Memórias das vivências profissionais de docentes: uma narrativa memorável sobre a escola e a educação do passado na comunidade Guajarense/Município de Curralinho - TAVARES, Cleide Pantoja (2022)
This work is based on the analysis of teaching in a historical context, from the Guajarense community in the municipality of Curralinho, in the State of Pará. Where the role of remote educator at the time of the dictatorship, with educators developing their works with more love, than support financial. In this context, this research was aimed at contextualizing the teaching life from the dictatorship period, with the inferences that such a policy influenced, as well as the person's view of retired teachers who exercised their function while they were still young. For that, the methodology of interview was elaborated, with questionnaires, photographs, conversations and observations of the places in the actuality. As a theoretical basis, we place the reflections on teacher education in Brazil and its devaluation. And it has as its theoretical basis the author Saviani (1987), which shows an education since the middle ages, where the center of knowledge was man himself. Also in Cury (1978), which shows how much one can use the old to build new knowledge. Other authors used are Gatti and Barreto (2009), which shows how much society does not value the educator according as they deserve, for the responsibility they carry. Among other important authors to this production.